2009
DOI: 10.1109/tvt.2009.2020578
|View full text |Cite
|
Sign up to set email alerts
|

EXIT-Chart Optimized Short Block Codes for Iterative Joint Source and Channel Decoding in H.264 Video Telephony

Abstract: Abstract-In this paper, we propose a family of short block codes (SBCs) designed for guaranteed convergence in soft-bitassisted iterative joint source and channel decoding, which facilitate improved iterative soft-bit source decoding (SBSD) and channel decoding. Data-partitioned (DP) H.264 source-coded video is used to evaluate the performance of our system using SBCassisted SBSD, in conjunction with recursive systematic convolution (RSC) codes for transmission over correlated narrow-band Rayleigh fading chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…3 Any bit-to-symbol mapping scheme different from the Gray-mapping is referred to as an anti-Gray mapping (AGM). EXIT outer curve of the Outer SISO module employing arbitrary SBC [2,6] LSSTC inner curves along with corresponding Trajectories at, EXIT outer curve of the Outer SISO module employing EXIT optimized SBC [2,6] LSSTC inner curves along with corresponding Trajectories at, The BER performance of the error protection schemes employed is presented in Figure 4. Its evident from Figure 4, that the LSSTC-SP-URC-SBC scheme using I system = 5 system iterations results in the best BER performance, when compared to I system = 4 and 3 for the same error protection scheme.…”
Section: System Performance Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Any bit-to-symbol mapping scheme different from the Gray-mapping is referred to as an anti-Gray mapping (AGM). EXIT outer curve of the Outer SISO module employing arbitrary SBC [2,6] LSSTC inner curves along with corresponding Trajectories at, EXIT outer curve of the Outer SISO module employing EXIT optimized SBC [2,6] LSSTC inner curves along with corresponding Trajectories at, The BER performance of the error protection schemes employed is presented in Figure 4. Its evident from Figure 4, that the LSSTC-SP-URC-SBC scheme using I system = 5 system iterations results in the best BER performance, when compared to I system = 4 and 3 for the same error protection scheme.…”
Section: System Performance Resultsmentioning
confidence: 99%
“…In [4], it was shown that the achievable ISCD performance can be improved by introducing artificial redundancy in the source coded stream. Therefore, in our proposed scheme we advocate a novel class of short block codes [6] invoked, in order to improve the attainable iterative decoding performance. A turbo-detected multidimensional Sphere Packing (SP) modulation scheme using two transmit antennas combined with Differentially encoded Space-Time Spreading (DSTS) is presented in [7].…”
mentioning
confidence: 99%
“…A number of layered video coding schemes [28] have been developed and some of them are adopted by recent video coding standards, for example the scalable video coding (SVC) [20] and data partitioned mode (DP) [9], [29], [30]. In the data partitioning mode, the data streams representing different semantic importance are categorized into a maximum of three bitstreams/partitions [31] per video slice, namely type A, type B and type C partition.…”
Section: ) Partition Mode Of H264mentioning
confidence: 99%
“…The APP p x i |y t 0 of the m-bit pixel x i , x i ∈ X m conditioned on the soft Markov process y 0 , …, y t may be formulated as p x i |y t 0 = p x i^y t 0 p y t 0 (13) where p x i^y t 0 indicates the probability that the soft Markov process y t 0 is received and the pixel value x i is transmitted at time instant i. Furthermore, the joint probability p x i^y t 0 may be further formulated as follows: …”
Section: References 8 Appendixmentioning
confidence: 99%